Socioenvironmental determinants of social interactions in a squatter settlement in istanbul - Erdo?an, Nevnihal; Sa?lamer, Gülsün; Dökmecí, Vedia F.; Dikbas, Attila (My University, 1996)
This paper investigates the socioenvironmental determinants of social interaction in a squatter settlement in Istanbul. The results of the study indicate that the origin of migrant families is the most important variable in stimulating social interaction among families. People from the same culture support each other in order to deal with the difficulties they face in city life. Another result is that proximity to others is correlated with the frequency of social interaction between families, which agrees with previous findings. At the same time, the spatial set-up of the neighborhood provides appropriate space to interact and opportunity for contact. On the other hand, education, age, and number of young children do not play a role in the social interaction in this particular neighborhood. Thus, cultural and spatial characteristics of the neighborhood are the most important variables for social interaction.
Keywords: Economic and social effects; Economics; Houses; Planning; Rural areas; Istanbul; Social interactions; Socioenvironmental determinants; Squatter settlement; Housing; social interaction; socioenvironmental determinants; squatter settlement; Turkey, Istanbul